Which of the following is developed to result in the answer of 1?

13−(7.42) 0

5 0+9 0

(−2.97)0

3(8 0)

15 answers

The expression that would result in the answer of 1 is:

3(8^0)
Which of the following shows the correct process of solving −30+4.5?

−30+4.5=−3⋅0+4.5=0+4.5=4.5

−30+4.5=−3+4.5=1.5

−30+4.5=−1⋅30+4.5=−1⋅1+4.5=−1+4.5=3.5

−30+4.5=(−3)0+4.5=1+4.5=5.5
The correct process of solving −30+4.5 is:

−30+4.5=−1⋅30+4.5=−1+4.5=3.5
Which of the following is an equivalent expression to 7(−5.3)0+4⋅9 when applying the Zero Power Rule? (1 point)

75.30+36

75.3+4⋅9

71+4⋅9

70+4⋅9
When applying the Zero Power Rule, any non-zero number raised to the power of zero is equal to 1. In this case, 7(−5.3)0 simplifies to 7(−5.3)(1) + 4⋅9. Since the expression in the parentheses after applying the Zero Power Rule is 1, the equivalent expression becomes:

7(−5.3) + 4⋅9

Therefore, the correct equivalent expression to 7(−5.3)0+4⋅9 when applying the Zero Power Rule is 7(−5.3) + 4⋅9
Which of the following is an equivalent expression to 7/(−5.3)0 +4⋅9 when applying the Zero Power Rule?

7/5.30 +36

7/5.3 + 4⋅9

7/1 + 4⋅9

7/0 + 4⋅9
When applying the Zero Power Rule, any non-zero number raised to the power of zero is equal to 1. In this case, (−5.3)^0 simplifies to 1. Therefore, the equivalent expression becomes:

7/1 + 4⋅9

Simplifying further, we have:

7/1 + 36

Which simplifies to:

7 + 36

Therefore, the correct equivalent expression to 7/(−5.3)^0 + 4⋅9 when applying the Zero Power Rule is 7 + 36.
Which of the following is an equivalent expression to 12(9−70)+(−29)0? (1 point)

12(9−1)−1

12(9−0)+0

12(9−1)+1

12(2)+1
An equivalent expression to 12(9−70)+(−29)0 is 12(9-0)+0.
Which of the following is an equivalent expression to 1/2(9−7 0)+(−29) 0? (1 point)

1/2(9−1)−1

1/2(9−0)+0

1/2(9−1)+1

1/2(2)+1
An equivalent expression to 1/2(9−7^0)+(−29)^0 is 1/2(9−1)+1.
Which of the following shows the correct process of solving −4 (3+12 0)+15 0 by generating an equivalent expression using the Zero Power Rule?

−4(3+12 0)+15 0=−4(3+1)+1=−4⋅4+1=−16+1=−15

−4(3+12 0)+15 0=−4(3+1)+1=−4⋅4+1=−4⋅5=−20

−4(3+12 0)+15 0 =−4(15)+15=−60+15=−45

−4(3+12 0)+15 0=−4(15)+1=−60+1=−59
The correct process of solving −4 (3+12^0)+15^0 by generating an equivalent expression using the Zero Power Rule is:

−4(3+12^0)+15^0 = −4(3+1)+1 = −4⋅4+1 = −16+1 = −15
1. (-2.97)0
2. The one that = 3.5
3.7/1 + 4 x 5
4. 1/2(9-1)+1
5. The one that = -15
Based on the options given, the correct answers are:

1. (-2.97)0 = 1 (according to the Zero Power Rule)
2. The one that = 3.5 is not provided, so it cannot be determined.
3. 7/1 + 4 x 5 = 7 + 20 = 27
4. 1/2(9-1)+1 = 4 + 1 = 5
5. The one that = -15 is not provided, so it cannot be determined.